From inception to implementation: an Argentine case study of teachers enacting early years inquiry-based science - Furman, Melina Gabriela (2017)
This study aimed to understand the process of implementing an early years inquiry-based science unit, focusing on the challenges teachers faced. A two-month professional development programme was implemented in two preschool classrooms. Two teachers with no inquiry-based science experience were provided with structured curriculum units and weekly pedagogical coach. Teachers observed coach-led model lessons (which were filmed and used during subsequent training) before implementing four 30-min lessons. Lessons and teacher interviews post-programme were filmed and their verbatim transcriptions analysed. Overall, teachers executed most basic elements from the units, providing students with opportunities to engage in scientific explorations. However, they struggled to use the activities for the collective construction of knowledge and development of scientific skills. Analysis of student?teacher dialogues shows that teachers rarely used student inputs to articulate prior knowledge with new concepts or to inform teaching, sometimes constructing misleading ideas about the nature of science as a result.